2017
DOI: 10.1515/shll-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

The role of social networks in the retention of /f/ aspiration among Mexican migrant workers in the Pacific Northwest

Abstract: AbstractFricative /f/ aspiration (i. e., /f/ -> [h] in words such as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Finally, the dense and multiplex social networks (Milroy 1980) that characterise this community provide a perfect environment for vernacular norm reinforcement. While this has been previously demonstrated for first-generation migrants in the native language of the origin community (see Van Buren 2017), this study shows that such vernacular norm reinforcement (in this…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Finally, the dense and multiplex social networks (Milroy 1980) that characterise this community provide a perfect environment for vernacular norm reinforcement. While this has been previously demonstrated for first-generation migrants in the native language of the origin community (see Van Buren 2017), this study shows that such vernacular norm reinforcement (in this…”
Section: Discussionsupporting
confidence: 42%
“…Previous work focusing on this variable (see Montoro del Arco 2017, Schwenter 1994, Schwenter et al 2008) will allow us to situate the present study in its wider stylistic and social context, while the relative homogeneity (in terms of linguistic background) of the speakers helps to maximise the usefulness of the data. Moreover, existing studies (see Cashman 2003, Evans 2004, Van Buren 2017 have demonstrated that vernacular norms can be maintained when migrants form dense and multiplex networks, as exemplified by the cultural association under examination.…”
Section: Theoretical Background: Contact Lvc and Migrationmentioning
confidence: 99%